Thymic development of human natural killer T cells: recent advances and implications for immunotherapy - Pellicci, Daniel G.; Tavakolinia, Naeimeh; Perriman, Louis; Berzins, Stuart P.; Menne, Christopher (Frontiers in Immunology, 2024)
Invariant natural killer T (iNKT) cells are a subset of lipid reactive, unconventional T cells that have anti-tumour properties that makes them a promising target for cancer immunotherapy. Recent studies have deciphered the developmental pathway of human MAIT and Vγ9Vδ2 γδ-T cells as well as murine iNKT cells, yet our understanding of human NKT cell development is limited. Here we provide an update in our understanding of how NKT cells develop in the human body and how knowledge regarding their development could enhance human treatments by targeting these cells.T cells are highly specialized lymphocytes that undergo a complex maturaOon and differenOaOon program that gives rise to disOnct T cell lineages with unique effector funcOons. ConvenOonal T cells that recognise pepOde anOgens presented by the major histocompaObility complex (MHC) undergo well characterized processes of anOgen receptor rearrangement followed by posiOve and negaOve selecOon in the thymus. They typically exit the thymus as naive progenitors, that can be primed upon primary anOgen encounter in the secondary lymphoid organs which confers funcOonal maturity and effector subset differenOaOon.The thymus also supports the development of several populaOons of unconvenOonal T cells that appear to undergo a decidedly disOnct maturaOon process. UnconvenOonal T cells typically recognise